Distribution and Abundance of the Blue Whale (Balaenoptera musculus indica) off Sri Lanka during the Southwest Monsoon 2018 - Liyanage U. S. P. Kirumbara; Jayasinghe R. P. P. Krishantha; Krakstad Jens-Otto; Arulananthan Kanapathipillai (Journal of Marine Science and Engineering, 2022)
Blue whales Balaenoptera musculus are the most abundant and widely distributed cetacean species in Sri Lankan waters. A vessel-based opportunistic line transect survey focusing on marine mammals was conducted in Sri Lankan waters between 24 June to 12 July 2018, while an ecosystem survey was performed by the R/V Dr. Fridtjof Nansen. The entire transect length was 2090 km within an area of 3895 km2. Overall, 72% (n = 57) of blue whale observations were group assemblages ranging between 1 and 5 individuals out of a total of 79 sightings. The largest aggregations of blue whales were recorded at the intersection of the submarine canyon off the coastline of Mirissa and busy shipping lanes between Dondra Head and Galle, where previous ship strikes were recorded. Overall, the average observed group size was 2.64 (CV, 12.34%; 95% CI, 2.07–3.38), the average group density was 0.0029 km−2 (CV, 35.96%; 95% CI, 0.00145–0.00610), and the total blue whale abundance within the survey area was 513 individuals (CV, 38.02%; 95% CI, 243–1083). These survey results fill vital knowledge gaps regarding the abundance and distribution of blue whales in Sri Lanka, which is essential for the establishment of management and conservation strategies.